Specific prostaglandins are produced in the migratory cells and the surrounding substrate to promote Drosophila border cell migration - Mellentine, Samuel Q.; Brown, Hunter N.; Ramsey, Anna S.; Li, Jie; Tootle, Tina L. (Frontiers in Cell and Developmental Biology, 2024)
A key regulator of collective cell migration is prostaglandin (PG) signaling. However, it remains largely unclear whether PGs act within the migratory cells or their microenvironment to promote migration. Here we use Drosophila border cell migration as a model to uncover the cell-specific roles of two PGs in collective migration. Prior work shows PG signaling is required for on-time migration and cluster cohesion. We find that the PGE2 synthase cPGES is required in the substrate, while the PGF2α synthase Akr1B is required in the border cells for on-time migration. Akr1B acts in both the border cells and their substrate to regulate cluster cohesion. One means by which Akr1B may regulate border cell migration and/or cluster cohesion is by promoting integrin-based adhesions. Additionally, Akr1B limits myosin activity, and thereby cellular stiffness, in the border cells, whereas cPGES limits myosin activity in both the border cells and their substrate. Decreasing myosin activity overcomes the migration delays in both ark1B and cPGES mutants, indicating the changes in cellular stiffness contribute to the migration defects. Together these data reveal that two PGs, PGE2 and PGF2α, produced in different locations, play key roles in promoting border cell migration. These PGs likely have similar migratory versus microenvironment roles in other collective cell migrations.